Please solve it for me!! Please...Maths
posted by Seth .
Solve for the value of x: 6log(x^2+1)x=0

6log(x^2+1)x=0
6 log(x^2 + 1) = x
log(x^2 + 1) = x/6
x^2 + 1 = e^(x/6)
wow ....
try Wolfram, since there is no "nice" way to solve this
http://www.wolframalpha.com/input/?i=x%5E2+%2B+1+%3D+e%5E%28x%2F6%29
It says: x = appr 0 or x = appr .169 or x = appr 45.93
testing:
if x = 0
LS = 6ln(1)  0 = 0 = RS > x = 0
if x = .169
LS = 6ln(1.028561)  .169
= .000035 and RS = 0 >not bad, x = appr .169
if x = 45.93
LS = 6ln(2110.5649)  45.93
= .0017.. close to zero > x = appr 45.93
all three answers work!!!!
Respond to this Question
Similar Questions

Math
Solve the system by addition or substitution. 3x – 4y = 8 6x – 2y = 10 Please get me on the correct track for 3x 4y =8 x=4, y=1 for 6x  2y =10 x= 2, y= 1 Solve one equation for x. 3x = 4y + 8 x = (4y + 8)/3 Insert that value … 
Maths
Solve for x: 6log(x^2 +1)  x = 0 
Please solve it.Logarithm
Please help me because I do not any idea in Logarithm topic.Solve for the value of X: 6log(x^2+1)=5 
Please help me solve it. Math
solve for the value of x: 6log (x^2+1)x=0. please help me because I do not have any idea in this topic. 
Please Ms Sue Help me! Alhorithm
Solve for the value of x: 6log(x^2+1)x=0. I can't even solve it. 
Maths
Solve for the value of x: 6log(x^2+1)x=0 
Math help please
1. Solve for x. 4(x  b) = x b = 4/3x b = 3/4x x = 4/3b x = 3/4b 2. Solve for y, then find the value of y when given x = 2. 6x = 7  4y 12 7/4 19/4 24 I need help solving these. Can you please explain how to solve these problems? 
Algebra 2
How do I solve these inequalities: e^3x>e^x1 6log (subscript of 4) x > 24 & how do I solve these: 8^x+1=3 e^x+2=50 8logx=16 I really don't understand how to solve these so can someone please explain them to me? 
math
Find x 1) 6log(down)10 x=1.6 2) e^4x=1.943 3) 1.3x10^4 x=4.7/x 6.3x10^3 4) 6lnx=1.6 5) x^2¡Ñ23y^2 = 1.78x10^32¡Ñz please help I really can't solve this problem. 
Math
Assume that x,y and a are positive numbers. Use the properties of logarithms to write the following expression  log a x^6 y^7 a. 42log a x+y b. 42log a x+7log a y c. 6log a x+42log a y d. 6log a x+7log a y e. 6log a x+6log a y